POTENSI AGROWISATA BERBASIS AGRILEISURE PERKEBUNAN KOPI DESA MELABUN, KABUPATEN BANGKA TENGAH - Yulius, Kevin Gustian; Deandra Ashtyn Pakasi; Samuel Musa Liha; Johannes Kurniawan (UHN IGB Sugriwa Denpasar, 2024)
Agrotourism is a tourist activity that is popularly carried out in Indonesia, which is an agricultural country. The study of agro-tourism produces agrileisure which is a conceptual framework for explaining the relationship between activities in agro-tourism. Coffee plantations in the Bangka Belitung Province, which is famous for its coffee drinking culture, were initially only for personal consumption without any other potential. This research seeks to identify the potential of coffee plantations as an agrileisure-based agro-tourism destination in Melabun Village, Central Bangka Regency. A qualitative approach with the type of case study was carried out, and data collection was carried out through structured interviews and observation for primary data, as well as a literature review for secondary data. Interviews were conducted with five main informants who were part of the village government and the provincial tourism office. The interview results are then narrated according to the agrileisure framework. The result is that Melabun Village does not yet have significant potential in terms of agriculture, and recreation and leisure. However, in the aspect of social change, Melabun Village has human resources that are quite ready to accept tourists, but still need education and training regarding tourism activities. The SWOT matrix was developed based on the results of the interviews to formulate a coffee plantation agro-tourism development strategy in Melabun Village. Promotion through exhibitions, social media, and building a brand image is recommended if Melabun Village wants to become a coffee plantation agro-tourism destination.